Dynamics of dry matter accumulation in corn hybrids of different maturity groups depending on foliar fertilization (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
This study presents and analyzes the results of a two-year investigation into the effect of foliar applications of various combinations of water-soluble fertilizers and anti-stress agents on the dynamics of dry matter accumulation and the mass of structural parts in corn hybrids of different maturity groups prior to harvest. Formulation of the problem. Despite the large number of scientific publications on corn fertilization approaches, the issue of evaluating the effectiveness of various foliar fertilization regimens – taking into account weather conditions, soil types, and the morpho-biotypes of corn hybrids – remains relevant. Furthermore, research into the impact of foliar fertilization on plant productivity and corn grain yield is a key step toward the development of environmentally friendly cultivation technologies. The purpose of the research. The aim of this study was to determine the effect of foliar applications of mixtures based on innovative water-soluble fertilizers and anti-stress agents, applied at different application rates, on the dynamics of dry matter accumulation and the mass of structural plant parts in maize hybrids of various maturity groups prior to harvest under the conditions of the Right-Bank Forest-Steppe of Ukraine. Research methods. The study was conducted in 2024 and 2025 at the “Horizon-2” agricultural enterprise in the Bilotserkivsky District of the Kyiv Region on deep black, medium loam, and loamy clay soils. A two-factor experiment was set up using the split-plot design with four replicates. The first-order plots (factor A) consisted of three corn hybrids: early-maturing P7818 (FAO 240); mid-early DKS 3730 (FAO 280); and mid-maturing DKS 4541 (FAO 380). The second-order plots (factor B) consisted of seven variants of foliar feeding with solutions based on complex water-soluble fertilizers and anti-stress medications. The area of the second-order plot was 140 m², and that of the reference plot was 100 m². Research results. It has been established that foliar feeding with solutions based on urea (N10), the water-soluble complex fertilizer Nanovit (corn) at a single dose of    1.5 l/ha, and the anti-stress agent Quantum AminoMax at a single dose of 1.0 l/ha has a positive effect on the growth and development of corn crops, resulting in higher plant dry matter and higher grain-bearing cob weight prior to harvest. In the treatment involving two foliar applications of this product combination, the dry matter yield per 1 m², as well as the dry matter yield per plant in all microphases monitored, was significantly higher compared to the control treatment where no foliar applications were made. From the early to the late growth stages, the difference in dry matter yield of corn plants under the influence of the tested foliar fertilization treatments increased, indicating a positive trend and an improvement in the effectiveness of these treatments. Specifically, on average over two years, in the treatment involving two foliar applications of this mixture of products, the dry matter mass of DKS4541 hybrid corn plants in the 19th microphase was 0.11 t/ha, or 5.1 % higher than the control, while in the 82nd microphase it was 1.96 t/ha, or nearly 14.0 % higher. A similar pattern was observed in the dry matter weight per plant. The addition of Partner zinc chelate fertilizer to the tank mix did not have a significant effect on increasing the dry matter yield of corn plants across all the hybrids studied. The pre-harvest grain-filled cob weight was also highest in the treatments that received two applications of urea-based mixtures, Nanovit fertilizer (corn), and the stress reliever Quantum AminoMax. On average across years and hybrids, it ranged from 103.5 to 105.4 g in these treatments, which is 9.3–11.2 g higher than in the control, although there was no significant difference among these treatments themselves. In all the growth stages during which measurements were taken, the mid-season hybrid DKS4541 (FAO 380) showed significantly higher values for both the dry matter yield per hectare and the dry matter yield per plant. In particular, during the 85th microphase, the dry matter yield of this maize hybrid averaged 16.35 t/ha across years and foliar fertilization treatments, while for the P7818 (FAO 240) and DKS3730 (FAO 280) hybrids, it was 12.96 t/ha and 13.88 t/ha, respectively. Conclusions. Overall, the highest dry matter yield across all growth stages was achieved by crops of the mid-season maize hybrid DKS4541 in the treatment involving two foliar applications during the 14-16th and 16-18th microphases according to the BBCH scale, using a mixture of urea (N10), the complex water-soluble fertilizer Nanovit (corn) (1.5 l/ha), and the stress reliever Quantum AminoMax (1.0 l/ha).
Keywords: corn; hybrid; dry plant weight; growth stages; complex water-soluble fertilizers; stress relievers; fertilization system